2022
DOI: 10.1167/iovs.63.5.34
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickening During Young Adulthood and Baseline Choroidal Thickness Predicts Refractive Error Change

Abstract: Purpose The purpose of this study was to explore the age-related change in choroidal thickness (ChT) and test the hypothesis that baseline ChT is predictive of refractive error change in healthy young adults. Methods Participants underwent spectral-domain optical coherence tomography (SD-OCT) imaging and autorefraction at 20 (baseline) and 28 years old. The enhanced depth imaging mode on the SD-OCT was used to obtain images of the choroid. Scans were exported from the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Previous studies revealed an association between AL and ChT; the present study further demonstrated 34.5% of the shortened AL could be explained by thickened ChT. AL shortening not only occurs in LLRL treatment, but also in the treatment of atropine or orthokeratology lens .…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies revealed an association between AL and ChT; the present study further demonstrated 34.5% of the shortened AL could be explained by thickened ChT. AL shortening not only occurs in LLRL treatment, but also in the treatment of atropine or orthokeratology lens .…”
Section: Discussionsupporting
confidence: 75%
“… 82 Choroidal thickness was evaluated in a subset of the above Australian birth cohort. 99 Myopia progression was associated with choroid thinning, whereas, overall, thickening was observed over an 8-year period. The association of baseline choroidal thickness with both myopic shift and axial elongation achieved borderline significance and was unrelated to refractive error at baseline.…”
Section: Factors Associated With Adult Myopia Onset and Progressionmentioning
confidence: 97%
“…Second, this study focused on choroidal changes in children 3 to 14 years old. Recent research by Lee et al 34 revealed that the choroid continued to thicken in young adults without myopic progression during the third decade of life. Extended observations covering a wider age range would provide further insights into the continuous evolution of the choroid throughout life.…”
Section: Discussionmentioning
confidence: 99%